Negotiation - Lewicki, Roy J. (Irwin/McGraw-Hill, 1999)
Offers a psychological exploration of the concepts and theories of bargaining and negotiation and the dynamics of interpersonal and intergroup conflict and its resolution. This book is aimed at a range of managers, and contains approaches readers can apply at work.